ADAPTATION OF THE BODY TO PREGNANCY (World Bulletin of Public Health, 2024)
The problem of complicated pregnancy, childbirth and the postpartum period is the essence of obstetric science. The study of this problem should be based on understanding the physiology of the uncomplicated course of the gestation process, on the one hand, and an approach to this problem from the standpoint of the whole organism, on the other. Pregnancy is one of the forms of life activity, and life is one of the natural phenomena. All natural phenomena are subject to the law, according to which they go through a certain cycle in their development: conception - development - formation. The last stage of this cycle is death, after which the natural phenomenon ceases to exist, merging with the environment. This law is also true for the phenomena of living nature. Life is a constant struggle with death, which is achieved by the continuous synthesis of information-rich macromolecules, the formation of cells with their complex organization, the formation of tissues and organs. The most important role in this process is given to the synthesis of protein as a substance of the most complex structure. It is proteins that play a primary role in the structure and function of the cell, being the molecular tools with the help of which genetic information is realized. In this paper, when we talk about hypertensive disorders, we mean “obstetric” hypertensive disorders, i.e. any obstetric complications
Keywords: body; hypertension; insulin; pregnancy